If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7/28)(6/27)=g
We simplify the equation to the form, which is simple to understand
(7/28)*(6/27)=g
Simplifying:
( + 0.25)*(6/27)=g
Simplifying:
( + 0.25)*( + 0.222222222222)=g
Reorder the terms in parentheses
multiplication of parentheses
( + 0.0555555555556)=g
Remove unnecessary parentheses
+ 0.0555555555556=g
We move all terms containing g to the left and all other terms to the right.
-1g=-0.0555555555556
We simplify left and right side of the equation.
-1g=-0.0555555555556
We divide both sides of the equation by -01 to get g.
g=0.0555555555556
| 4a+6a+2a= | | (4z+2)+(69-4z+y+19)=90 | | z+13/4=x | | 4x^2+5x=-10 | | 238.64=3.14D | | X^2-30x+135=0 | | 5x+15=6x+10 | | -n/5-16=-21 | | 4x+13=z*z | | -4.7-2.3y= | | X^2+4x+11=-10 | | -5/6x=7/12 | | 0.5x+0.6=0.2x-0.9 | | 3.55y-7.2y= | | 27-2x=7x | | 6b-b=56 | | 4x^4-2x^2+6=0 | | X^2-9x=29 | | (5X-7)/3=X+5 | | 2n-3[2]=53 | | -2(-2h+6)=-26 | | Y=2-6 | | (4y-2)+3y= | | (4z+2)+(y+19)=90 | | 4p^2-p+3=0 | | (3x-4)=0 | | 3(2x-1)-5=2(2x+3)+4 | | 23z-13z=15 | | 5/7x=45 | | 4x^4-2x^2+8=2 | | -(x-7)+5/3=2(x+9) | | 3x-4y=z*z |